Responses of Soil Carbon Pools, Enzymatic Activity, and Crop Yields to Nitrogen and Straw Incorporation in a Rice-Wheat Cropping System in North-Western India - Sharma, Sandeep; Singh, Pritpal; Kumar, Sandeep (Frontiers in Sustainable Food Systems, 2020)
Fertilizer-N application and straw incorporation impacts crop productivity due to changes in total organic carbon (TOC), its labile pools and the soil enzymatic activity. A field experiment was established (in 2010) to study the effect of fertilizer-N application (0, 90, 120, and 150 kg N ha−1) and rice straw (RS) incorporation (0, 5.0, 7.5, and 10 Mg ha−1) on crop yield, C input, TOC and its labile pools and soil enzymatic activity under rice (Oryza sativa L.)—wheat (Triticum aestivum L.) cropping system (RWCS) in north-western India. Data showed that fertilizer-N application and RS incorporation significantly (p < 0.05) increased the rice and wheat grain yield, compared with control (CK). However, the RS incorporation alone did not impact crop yields. The sustainable yield index (SYI) for wheat was significantly lower with RS incorporation alone as compared with the other treatments. For rice, SYI was significantly higher for RS7.5N120, and was non-significant compared with the RS10.0N120. Annual total C input in soil plow layer (0–15 cm) under RWCS varied between 3.34 and 9.78 Mg C ha−1, which was higher by 4.4 Mg C ha−1 yr−1 ( 2.3-times) in RS10.0, compared with CK. The conjoint application of fertilizer-N and RS incorporation (RS10.0N150) significantly increased the TOC, water extractable organic C (WEOC), hot water C (HWC), microbial biomass C (MBC) and basal soil respiration (BSR) due to increased soil enzymatic activity viz. dehydrogenase activity (DHA), fluorescein diacetate (FDA) and alkaline phosphatise (Alk-P). A significant increase in potassium permanganate oxidizable C (KMnO4-C) with RS incorporation under RS10.0N150 increased the C management index (CMI), and hence the soil quality. The inter-correlations between highly weighted soil variables among different principle components (PCs) revealed that KMnO4-C in PC1, FDA activity in PC2, and BSR in PC3 with the highest correlation were the sensitive indicators for assessing soil quality in a RWCS.